PENGARUH PENGGUNAAN LEMAK SAPI, MINYAK KELAPA DAN MINYAK KEDELAI DALAM PAKAN TERHADAP PERFORMA PRODUKSI AYAM PEDAGING - A. B. A Mardhotillah; Hariyadi Darmawan; I. H. Djunaidi; L. C. Hsia; Y. C. Chen (Universitas Tribhuwana Tunggadewi, 2020)
This experiment was conducted to evaluate the effect of various fat sources and their combination (coconut oil and soybean oil) on growth performance of broiler. A total of 80 one-day old female 1-d-old Arbor Acres were randomly assigned into four groups (4 treatment) with 10 replicates (6 birds per pen) within 42 days. The experimental groups consisted of four treatment of diets: 1) a basal-diet containing beef oil (BO), 2) a basal diet containing coconut oil (CO), 3) a basal diet containing soybean oil (SO), and 4) a basal diet containing coconut oil and soybean oil (CO+SO) as were used. Performance data were obtained during the feeding period. The result was shown that using combination of medium chain fatty acid and unsaturated fatty acid (CO+SO) were increased growth performance demonstrated by highest bodyweight (59.62 g) compared with other treatments (P 0.05) throughout the experimental period (0-42 days). The lower group for feed conversion ratio was obtained in the diet containing beef oil (BO) compared with other groups (1.32; P 0.05). Feed consumption and bodyweight have significantly different (P 0.05) but not different for feed conversion ratio (P 0.05). It can be concluded that feeding combination CO+SO in the diet may improve the performance of broiler.Beef oil; broiler; coconut oil; growth performance; soybean oil